2002
DOI: 10.1007/s00586-002-0481-z
|View full text |Cite
|
Sign up to set email alerts
|

Total disc replacement arthroplasty using the AcroFlex lumbar disc: a non-human primate model

Abstract: Using a non-human primate model, the current study was undertaken to investigate the efficacy of the AcroFlex lumbar disc as an intervertebral disc prosthesis, based on biomechanical, histopathologic and histomorphometric analyses. A total of 20 mature male baboons (Papio cynocephalus, mean weight 30 kg) were randomized into two equal groups based on post-operative time periods of 6 (n=10) and 12 months (n=10). Each animal underwent an anterior transperitoneal surgical approach to the lumbar spine, with interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The Flexibility test method has been described [13], and used in many studies of fusion devices [2,4,7,12], and non-fusion devices [5,10]. In the present study, the input was unconstrained pure moment applied in flexion/extension: maximum of 8 Nm in the presence of 400 N follower load [16].…”
Section: Flexibility Test Methodsmentioning
confidence: 99%
“…The Flexibility test method has been described [13], and used in many studies of fusion devices [2,4,7,12], and non-fusion devices [5,10]. In the present study, the input was unconstrained pure moment applied in flexion/extension: maximum of 8 Nm in the presence of 400 N follower load [16].…”
Section: Flexibility Test Methodsmentioning
confidence: 99%
“…The regions of trabecular contact were subsequently traced, quantified in pixels, and expressed as a percentage of the total endplate area (% ingrowth = apparent bone contact area/gross total endplate area). The above quantitative evaluation method has been widely used in several previous studies [ 11 – 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The first version, a precursor of the Freedom disc named Acroflex (Depuy, Acromed Inc. Raynham Mass. ), was an unconstrained lumbar design consisting of porous coated titanium endplates with a polyolefin rubber core [25]. Although the rubber was extensively tested for its fatigue life and wear properties [26], the results of this study demonstrated rubber tears in 36% of the patients [27].…”
Section: Endplate Sandwiched -Monoblockmentioning
confidence: 99%